REFLECTION AND TRANSMISSION IN THE IONOSPHERE CONSIDERING COLLISIONS IN A FIRST APPROXIMATION - Yesil, A.; Aydogdu, M.; Elias, A. G. (E M W Publishing, 2008)
Reflection and transmission coefficients (R and T) of high frequency waves propagating in the ionosphere are studied taking collisions into account. This was done approximating the expression (1 + Z(2))(-1) in the refractive index using binomial expansion and neglecting terms of order higher than Z(2), where Z is the ratio between the electron collision frequency and the wave frequency. R and T height profiles were assessed using the International Reference Ionosphere, IRI, to estimate the ionosphere plasma parameters. Although no significant differences are found between the estimation with and without collisions, the method employed to include collisions may be useful for other purposes where collisions should be taken into account.